2020
DOI: 10.47602/jpsp.v4i2.225
|View full text |Cite
|
Sign up to set email alerts
|

Expressive flexibility and resilience among U.S. military college students: Evaluating the enhancing and suppressing of emotions and resilience

Abstract: Significant research has confirmed the necessity to better comprehend psychological constructs that are essential in predicting and influencing human performance, in particular, assessing expressive flexibility and resilience. However, limited research has investigated the relationships that exist between these two constructs that are critical protective factors in facilitating the mental health and the well-being of individuals. Through a number of structural equation modeling (SEM) techniques, the current en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(86 reference statements)
2
4
0
Order By: Relevance
“…Resilience is a powerful personal resource that helps people to cope with the pandemic challenges (Yıldırım et al, 2020a ), which in turn improves their mental health and well-being. Consistent with the results of this study, past research showed that resilience was significantly associated with positive (e.g., life satisfaction, psychological well-being) and negative (e.g., depression, anxiety) mental well-being indicators (Bonanno, 2004 ; Arslan, 2015 ; Arslan and Balkis, 2016 ; Kansky and Diener, 2017 ; Cohen et al, 2020 ; Georgoulas-Sherry, 2020 ; McDonnell and Semkovska, 2020 ; Yıldırım and Arslan, 2020 ; Yıldırım and Çelik Tanrıverdi, 2020 ). For example, Gao et al ( 2017 ) reported that resilience was a significant predictor of better general well-being and lower mental health problems.…”
Section: Discussionsupporting
confidence: 89%
“…Resilience is a powerful personal resource that helps people to cope with the pandemic challenges (Yıldırım et al, 2020a ), which in turn improves their mental health and well-being. Consistent with the results of this study, past research showed that resilience was significantly associated with positive (e.g., life satisfaction, psychological well-being) and negative (e.g., depression, anxiety) mental well-being indicators (Bonanno, 2004 ; Arslan, 2015 ; Arslan and Balkis, 2016 ; Kansky and Diener, 2017 ; Cohen et al, 2020 ; Georgoulas-Sherry, 2020 ; McDonnell and Semkovska, 2020 ; Yıldırım and Arslan, 2020 ; Yıldırım and Çelik Tanrıverdi, 2020 ). For example, Gao et al ( 2017 ) reported that resilience was a significant predictor of better general well-being and lower mental health problems.…”
Section: Discussionsupporting
confidence: 89%
“…Both models are statistically significant, but it can be seen in Table 3 that calculated test values (χ 2 , ECVI, AIC, and BCC) for Model 2 demonstrated a somewhat better model fit when compared to Model 1 test values. In general, should be noted that the RMSEA value above 0.08 is acceptable, but for the models presented, this value is below 0.08, proving that the fit guides meet the necessities for SEM [63,64]. In addition, the differences between test values of these models are not essential, for example: ∆CFI is 0.003 and ∆IFI is 0.003, ∆TLI is 0.038 and ∆ECVI is 0.005, which do not surpass the critical value [60].…”
Section: Comparable Information Between Overall Fit Of Designed Modelsmentioning
confidence: 76%
“…In this context, the concept of expressive flexibility was proposed to understand one’s ability to enhance and suppress emotional expressions to adapt to contextual demands [ 5 , 15 , 16 ]. Studies showed that resilience was positively associated with expressive flexibility [ 17 ], emotional flexibility [ 18 ], and coping flexibility [ 13 ]. Some researchers even identified expressive flexibility as one key component of resilience, highlighting the importance of flexibility in the regulation of emotions [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%